The relationship between fundamental motor skills and game specific skills in elite young soccer players - Kokstej, J.; Musalek, M. (Journal of Physical Education and Sport, 2019)
Game specific motor skills develop the foundation of the game of football. The importance of fundamental motor skills as a substantial basis of sport-specific motor skills is generally accepted. However, up until now, research on the relationship between fundamental and specific motor skills in soccer players has been missing. The aim of this study, therefore, was to investigate the relationship between fundamental motor skills and game specific motor skills in elite young football players (N = 24; mean age 11.6 ± 0.4 years). Football specific dribbling and shooting test as a game-specific motor skills and The Test of Gross Motor Skills - 2nd edition (TGMD-2) as a set of fundamental motor skills were used. We found a strong relationship between TGMD-2 and game-specific motor skills (r = 0.62 - 0.70). The horizontal jump and catch were found to be the best predictors of game-specific motor skills (F(2, 21) = 21.13, p < 0.001, R2 = 0.64). The players reported the poorest performance in several subtests: striking a stationary ball, overhand throw, underhand roll, and horizontal jump. These results demonstrate the need for a certain level of both fine and gross fundamental motor skills in order to acquire game-specific motor skills. Youth coaches should emphasize adequate development of FMS, particularly during early and middle childhood. Coaches should especially develop and improve a wide range of fundamental motor skills as building blocks of more complex and difficult, football-specific, motor skills during the long-term training process.